Student Perceptions of Using Game-Based Learning to Enhance English Vocabulary Acquisition - Fauziah Fatimah Az-zahra Marwan Putri (Teaching and General Education Studies, 2025)
This study investigates student perceptions of using Game-Based Learning (GBL) to enhance English vocabulary acquisition among sixth-semester students of the English Education Program at Silampari University. Rooted in constructivist and multimedia learning theories, this research applies a quantitative method using a Likert-scale questionnaire to collect data from 13 purposively selected participants. The findings reveal that students perceive GBL as a highly motivational and engaging approach that supports vocabulary learning through interactivity, contextualization, and immediate feedback. While most students expressed positive attitudes toward GBL, moderate responses regarding vocabulary retention and confidence indicate the need for supplementary reinforcement strategies. Overall, the study underscores the effectiveness of GBL as a complementary method in English language teaching and suggests further pedagogical innovation tailored to learner needs.